Frost promotes the pathogenicity of Pseudomonas syringae pv. actinidiae in Actinidia chinensis and A. deliciosa plants. (9th May 2013) - Ferrante, P.; Scortichini, M.
<x xml:space="preserve">Abstract</x> Frost occurs in all major areas of cultivation, presenting a threat for the production of kiwifruit crops worldwide. A series of experiments were performed on 1‐year‐old, potted plants or excised twigs of Actinidia chinensis and A. deliciosa to verify whether strict relationships exist between bacterial canker outbreaks from Pseudomonas syringae pv. actinidiae (Psa) attacks and the occurrence of autumn and winter frost events. The association between the occurrence of autumn frost and the sudden outbreak of bacterial canker in A. chinensis in central Italy has been confirmed. Both autumn and winter frosts promote Psa multiplication in the inoculated twigs of both species. The day after the frost, reddish exudates oozing from the inoculation sites were consistently observed in both species, and Psa was re‐isolated in some cases. During the thawing of both A. deliciosa and A. chinensis twigs, the 2‐cm upward and downward migration of Psa from the inoculation site was observed within 3 min, and the leaves were consistently colonized with the pathogen. A consistent brown discoloration, accompanied with a sour‐sap odour, was observed throughout the length of the excised twigs of both Actinidia species after Psa inoculation and winter frost. Psa inoculation induced a remarkably higher necrosis in excised twigs that were not frozen compared with P. s. pv. syringae inoculation. Antifreeze protection using irrigation sprinklers did not influence the short‐term period of Psa and P. s. pv. syringae multiplication in both A. deliciosa and A. chinensis twigs. Thus, the damage from frost, freeze thawing and the accumulation of Psa in Actinidia twigs promotes the migration of the pathogen within and between the orchards. Taken together, the results obtained in this study confirmed that A. deliciosa is more frost tolerant than A. chinensis, autumn frosts are more dangerous to these crops than winter frosts, and in the absence of Psa, young kiwifruit plants remain sensitive to frost.